PERSEPSI SISWA TERHADAP INTEGRASI GAMIFIKASI DALAM PEMBELAJARANBAHASA INDONESIA: STUDI KUALITATIF DI SMK MUKHTAR SYAFA’AT BLOKAGUNG - Hasnaur Rif’ah; Muhammad Hasbullah Ridwan (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to evaluate students’ perceptions of gamification in Indonesian language learning at SMK Mukhtar Syafa’at Blokagung, analyze its effects on motivation and participation, and identify potential challenges and solutions. A qualitative approach with a case study design was employed. Data were collected through observation, semi-structured interviews, and documentation. The results indicate that most students responded positively to gamification. Platforms such as Kahoot! and Wordwall created an enjoyable learning atmosphere, enhanced peer interaction, and boosted students’ intrinsic motivation. Challenges included limited access to devices and unstable internet connectivity. Thematic analysis reveals that gamification supports students' psychological needs as described in Self- Determination Theory. The study concludes that gamification has the potential to improve learning quality in pesantren-based education settings, provided it is adapted to religious values, local culture, and digital infrastructure readiness. Ethical implications highlight the importance of inclusive and meaningful gamified learning design.